Karakteristik Rumah Tangga Nelayan Miskin di Kecamatan Sungai Limau Kabupaten Padang Pariaman - Mayasari, Melly; Arjoni, Arjoni (Greenation Publisher & Yayasan Global Resarch National, 2023)
Abstract: The aim of the study was to describe the characteristics of poor fishing households in Sungai Limau District, Padang Pariaman Regency in relation to the number of children born alive (ALH), education level, working hours, and utilization of health services. This study found that (1) the average number of children born alive (ALH) in poor fishing households in Sungai Limau District was 7 people. (2) The most dominant level of education reached by poor fishing households in Sungai Limau Sub-District is Elementary School, not completing and graduating. (3) Fishing activities in Sungai Limau District are carried out every day, where the working hours of the most dominant head of the family are 10-12 hours/day with the distance traveled to go to sea 4 miles. (4) The health service frequently visited by poor fishing households when a member of the household is sick is the puskesmas service. Abstrak: Tujuan penelitian untuk mendeskripsikan karakteristik rumah Tangga nelayan miskin di Kecamatan Sungai Limau Kabupaten Padang Pariaman terkait dengan jumlah Anak Lahir Hidup (ALH), tingkat pendidikan, jam kerja dan pemanfaatan layanan kesehatan. Penelitian ini menemukan bahwa (1) Rata-rata Anak Lahir Hidup (ALH) pada rumah tangga nelayan miskin di Kecamatan Sungai Limau adalah 7 orang. (2) Jenjang pendidikan yang ditempuh rumah tangga nelayan miskin di Kecamatan Sungai Limau paling dominan adalah tidak tamat dan tamat SD. (3) Kegitan melaut di Kecamatan Sungai Limau dilakukan setiap hari, dimana Jam kerja kepala keluarga yang paling dominan adalah 10 – 12 jam/hari dengan jarak yang ditempuh untuk melaut adalah 4 mil. (4) Layanan kesehatan yang sering dikunjungi oleh rumah tangga nelayan miskin jika ada anggota rumah tangga yang sakit adalah layanan puskesmas.